ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN CERITA FIKSI ANAK PADA SISWA KELAS IV MI ATTAQWA 42 PULO KENDAL BEKASI - Hurin Nuri Assyifa; Hafizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the reading comprehension ability of fictional texts among fourth-grade students at MI At-Taqwa 42 Pulo Kendal, Bekasi. The research employed a descriptive quantitative approach using a multiple-choice test as the instrument, based on five reading comprehension indicators: (1) identifying the main idea, (2) understanding difficult vocabulary, (3) answering content-based questions, (4) retelling the text in one’s own words, and (5) drawing conclusions from the text. Data were collected through observation, interviews, documentation, and testing, involving 21 student participants. The data were analyzed descriptively and presented narratively. The findings revealed that the highest average score was achieved in the ability to identify main ideas (89%), followed by drawing conclusions (85%), answering content-based questions (80%), and both understanding difficult vocabulary and retelling the story (71%). Overall, students demonstrated good reading comprehension ability, especially in understanding the core message and concluding the story. However, weaknesses were identified in vocabulary mastery and the ability to retell stories using their own words. These findings may serve as a reference for developing more effective reading instruction strategies, particularly in teaching fictional texts at the elementary level.